Profiles of Men’s Rape Myth Beliefs and the Association With Rape Proclivity - O’Connor, Julia (Journal of interpersonal violence, 2023)
The two constructs of rape myth acceptance (RMA) and rape proclivity are associated with sexual violence (SV) perpetration. Further understanding these constructs can help improve prevention efforts aimed at reducing SV perpetration. Latent profile analysis was conducted to examine typologies of RMA among 474 incoming college men and found that male college students can be categorized into four profiles. Some groups endorsed lower or mid-levels of rape myths (RMs) and others endorsed higher levels of some or all RMs, indicating the heterogeneity of RM beliefs. And within each subgroup of college men’s RMA, intention to join an all-male sports team and/or a fraternity (two risk factors) and bystander attitudes (a protective factor) were examined as covariates in the model. Bystander attitudes appear to act as a protective factor as they are higher among profiles of men with lower RMA. Furthermore, this study examined the four subgroups (latent profiles) of college men based on their RMA to examine whether membership within each subgroup/profile is differentially associated with rape proclivity. The findings indicate that subgroups of men with high levels of RMA have higher mean rape proclivity scores compared to the subgroup of men with the lowest level of RMA. Implications for prevention programming tailored for high-risk groups of men, based on their RMA beliefs, as well as possible future research within this area are discussed.